EFL Motivational Strategies in Teaching Reading - Fauzana Azya Arifta (Journal of English Language and Education, 2021)
This study aims to determine the strategies the teacher uses in motivating students to read in English lessons. This study uses a qualitative case study of microethnography to obtain data. This research was conducted online to the English teacher and five students'. in collecting data using interviews and observation. The results of the research found that teachers have good English, provide motivational strategies to students in reading, motivate students by giving interesting stories, and provide assessments or praise to increase students' reading enthusiasm.